1981
DOI: 10.1111/j.1365-2621.1981.tb14567.x
|View full text |Cite
|
Sign up to set email alerts
|

Textural Characteristics of Beef: Effects of the Heating System

Abstract: Textural characteristics of beef semitendinosus roasts heated in 93 and 149°C ovens to 60 and 70°C were compared with those of small samples of semiten~linosus heated as cylindrical cores in glass tubes in a water bath. Tie small samples were heated to the same endpoint temperatures as the roasts were at rates comparable to heating at the two oven temperatures. Cooking losses varied with heating method and in sorte cases with endpoint temperature and rate of heating. Heating method did not affect the textural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Thermal processing‐based changes in meats are connected with the changes in meat texture (Palka and Daun 1999). Influence of thermal processing on the textural properties and sensory quality of meat and meat products has been previously studied for changes in connective tissue, soluble proteins and myofibrillar proteins (Action 1972; Brady and Penfield 1981; Palka and Daun 1999; Murphy and Marks 2000; Combes et al. 2002; Ma and Ledward 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal processing‐based changes in meats are connected with the changes in meat texture (Palka and Daun 1999). Influence of thermal processing on the textural properties and sensory quality of meat and meat products has been previously studied for changes in connective tissue, soluble proteins and myofibrillar proteins (Action 1972; Brady and Penfield 1981; Palka and Daun 1999; Murphy and Marks 2000; Combes et al. 2002; Ma and Ledward 2004).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that compression as measured by the Instron and adhesion mea-surements made on muscle samples were highly related, as were the peak (maximum) force measurements made with the Warner-Bratzler shear device and fiber tensile measurements. Other researchers have used instrumental methods (Brady and Penfield, 1981;Brady and Hunecke, 1985;Zayas and Naewbanij, 1986) and evaluated such parameters as shear firmness and shear cohesiveness. Shear firmness is defined as the slope of a line from the origin of the curve to its peak, expressed in kg/min.…”
Section: Introductionmentioning
confidence: 99%
“…Penfield and Meyer (1975) showed decreases in shear values after cooking beef semitendinosus to 6o"C, and Laakkonen et al (1970) and Laakkonen (1973) reported several studies which showed decreases in shear values of various beef muscles heated between 50"-6o"C, due to the shrinkage of intramuscular collagen. In other studies (Paul et al, 1973;Moller, 1980-81;Brady and Penfield, 1981) heating above 60°C showed no effect of ultimate temperature on shear values. For trimmed RSB, the percent extractable collagen showed no distinct variation with temperature except for a decrease at 35°C (Fig.…”
Section: Resultsmentioning
confidence: 84%